Albert Lauterbach. Enterprise in Latin America : business in a developing economy. Ithaca, New York : Cornell University Press, 1966. 207 p. - Pontes, Manuel (El Colegio de México A.C., 1967)
ALBERT LAUTERBACH, Enterprise in Latin America; Business in a Developing Economy. Ithaca, New York: Cornell University Press, 1966.